Achieving axial fan sound reduction with micro-perforated absorbers - Floss, Sebastian; Czwielong, Felix; Krömer, Florian; Becker, Stefan; Kaltenbacher, Manfred (Fortschritte der Akustik - DAGA 2019 45. Deutsche Jahrestagung für Akustik, 18.-21. März 2019 in Rostock, 2019)
Aeroacoustic noise sources, especially under distorted flow conditions, are one of the main causes of sound emissions on an axial fan geometry layout in a complex ventilation system scenario. To attenuate sound, one can either modify the aeroacoustic sources by changing the fan blade geometry, or one can use passive absorbing mechanisms which are applied as wall lined structures up- and downstream of the fan. We propose the application of MPAs (micro-perforated absorbers) in the tipflow region of the fan to account for tonal components of the emitted sound pressure spectrum. Possible near-field effects on the absorbing structure will be investigated by simulating MPAs with the Johnson-Champoux- Allard approach in a Finite Element (FE) - framework . This is followed by measurements at an experimental test section where we will investigate the effect of the MPA structure on pressure drop, performance and the overall emitted sound pressure level of the fan.<br
Keywords: MPP; MPA; Akustik; Absorber; Axialventilator

Active Turbulence Grid-Controlled Inflow Turbulence and Replication of Heat Exchanger Flow Fields in Fan Applications - Czwielong, Felix; Becker, Stefan (International Journal of Turbomachinery, Propulsion and Power, 2023)
A novel active turbulence grid of the Institute of Fluid Mechanics at FAU Erlangen-Nuremberg is introduced. The focus of this grid is not on basic investigations of fluid mechanics, as is usually the case with active turbulence grids, but the generation of defined inflow conditions for axial fans. Thus, by means of the active turbulence grid, individual turbulence characteristics in the flow to the fan can be changed; therefore, fundamental interactions between the flow mechanics at the axial fan and the sound radiation can be analyzed. In addition, the replication of the flow fields of heat exchangers by the active turbulence grid is the focus of the investigations. The investigations showed that it is possible to use the active turbulence grid to generate defined inflow conditions for axial fans. It was also possible to reproduce the heat exchanger flow fields both for the mean turbulence values and for the spatial distributions. It was found that the grid induces tonal components due to the drive motors, but also that the inherent noise has no significant influence on the spectrum of the fans under investigation. Based on selected turbulence characteristics, direct correlations were found between the spatial distribution of the turbulence level and sound radiation at the first blade passing frequency of the axial fan. As the variance of the turbulence level increases, the sound radiation of the tonal components becomes more pronounced. The total sound pressure level, however, is mainly determined by the low-frequency broadband sound. A linear relationship between the spatial mean value of the turbulence level and the total sound pressure level was found for the investigated axial fan.
CRIS-Team Scopus Importer:2023-04-07
Keywords: active turbulence grid; axial fan noise; controlled inflow; heat exchanger; inflow turbulence; leading edge noise

Aerodynamic and aeroacoustic properties of axial fan blades with slitted leading edges - Ocker, Christof; Czwielong, Felix; Chaitanya, Paruchuri; Pannert, Wolfram; Becker, Stefan (Acta Acustica, 2022)
A detailed experimental analysis of the aerodynamic and aeroacoustic properties of flat-plate axial fans with slitted leading edges is performed. The sound emissions of five slitted leading edge designs are measured at a constant rotational speed and at a constant total-to-static pressure rise of the fans. For both cases, the fan blades with slitted leading edges reduce the turbulence interaction noise and lead to a reduction of the overall sound pressure level for volume flow rates above 0.6 m(3) s(-1) compared to an axial fan with solid leading edges. The far-field noise analysis shows that the slits result in a noise reduction for frequencies below 2 kHz and a noise increase above 2 kHz. In addition, sound source localization is conducted with a microphone array and rotating beamforming methods are applied. The identified sound source distributions prove that slitted leading edges reduce turbulence interaction noise, but generate broadband noise in the fan blades ' trailing edge regions. The maximum sound reduction due to the slits could be detected at a dimensionless frequency of fh/(w) over bar approximate to 0:5, where f is the frequency, h is the height of the slit and (w) over bar is the mean relative inflow velocity. The noise reduction mechanism on axial fan blades corresponds well to previous investigations on flat-plate airfoils with slits.
CRIS-Team WoS Importer:2022-11-04

AERODYNAMICS AND AEROACOUSTICS OF LEADING EDGE SERRATION IN LOW-SPEED AXIAL FANS WITH FORWARD SKEWED BLADES - Tieghi, Lorenzo; Czwielong, Felix; Barnabei, Valerio F.; Ocker, Christof; Delibra, Giovanni; Becker, Stefan; Corsini, Alessandro (Proceedings of the ASME Turbo Expo, 2023)
Low-speed axial fans must comply with a wide number of standards and normative restrictions, often related to the maximum noise emission levels. Among the noise control techniques in axial fans, skewed fan blades and leading edge (LE) serrations have been found to be effective in LE noise control, which represents one of the dominant phenomena in axial fan broadband emissions. However, these solutions are usually applied separately, and literature is scarce on systematic studies on the coupling of the two modifications. In this work, a campaign of experimental measurements was conducted on unskewed and forwardskewed axial fan blades with and without leading-edge serrations. The tests were peiformed in undisturbed inflow conditions. The flow field and the turbulence characteristics were measured using 3D hot-wire anemometry. The suction-side sound radiation of the fans was measured with microphones in an anechoic chamber. In addition, the rotating beamfonning method was used to localize the sound sources at the axial fans. It was found that, regardless of the blade skew, the leading edge serrations lead to a reduction of the sound pressure level, whereby the aerodynamic properties of the fan decrease. At the same operating points, which were achieved by adjusting the rotational speed, the sound radiation through the leading edge serrations could be reduced at high-volumeflows. This effect was more pronounced with the unskewed rotor, which indicates that the positive effect of the serrations is reduced by the already optimized shape of the forward skewed fan blade. Based on the experimental results, the four geometries werefurther considered for numerical investigations to understand how the serrations affect the fan operations and the overall aerodynamics of the rotor. All four geometries were simulated with RANS approach at the duty point to derive aflow survey and better understand the dynamics driven by serrations and blade skewing.
CRIS-Team Scopus Importer:2023-12-01

Aerodynamics and Aeroacoustics of Leading Edge Serration in Low-Speed Axial Fans With Forward Skewed Blades - Tieghi, Lorenzo; Czwielong, Felix; Barnabei, Valerio F.; Ocker, Christof; Delibra, Giovanni; Becker, Stefan; Corsini, Alessandro (Journal of Engineering For Gas Turbines and Power-Transactions of the Asme, 2024)
Low-speed axial fans must comply with a wide number of standards and normative restrictions, often related to the maximum noise emission levels. Among the noise control techniques in axial fans, skewed fan blades and leading edge serrations have been found to be effective in leading edge noise control, which represents one of the dominant phenomena in axial fan broadband emissions. However, these solutions are usually applied separately, and literature is scarce on systematic studies on the coupling of the two modifications. In this work, a campaign of experimental measurements was conducted on unskewed and forward-skewed axial fan blades with and without leading-edge serrations. The tests were performed in undisturbed inflow conditions. The flow field and the turbulence characteristics were measured using three-dimensional hot-wire anemometry. The suction-side sound radiation of the fans was measured with microphones in an anechoic chamber. In addition, the rotating beamforming method was used to localize the sound sources at the axial fans. It was found that, regardless of the blade skew, the leading edge serrations lead to a reduction of the sound pressure level, whereby the aerodynamic properties of the fan decrease. At the same operating points, which were achieved by adjusting the rotational speed, the sound radiation through the leading edge serrations could be reduced at high-volume flows. This effect was more pronounced with the unskewed rotor, which indicates that the positive effect of the serrations is reduced by the already optimized shape of the forward skewed fan blade. Based on the experimental results, the four geometries were further considered for numerical investigations to understand how the serrations affect the fan operations and the overall aerodynamics of the rotor. All four geometries were simulated with RANS approach at the duty point to derive a flow survey and better understand the dynamics driven by serrations and blade skewing.
CRIS-Team Scopus Importer:2023-12-01

A Finite-Element-Simulation Workflow and First Results of the Aero- and Vibro-Acoustic Signature of an Enclosed Centrifugal Fan - Heidegger, Patrick; Czwielong, Felix; Schoder, Stefan; Becker, Stefan; Kaltenbacher, Manfred (SAE Technical Papers, 2024)
Centrifugal fans are applied in many industrial and civil applications, such as manufacturing processes and building HVAC systems. They can also be found in automotive applications. Noise-reduction measures for centrifugal fans are often challenging to establish, as acoustic performance may be considered a tertiary purchase criterion after energetic efficiency and price. Nonetheless, their versatile application raises the demand for noise control. In a low-Mach-number centrifugal fan, acoustic waves are predominantly excited by aerodynamic fluctuations in the flow field and transmit to the exterior via the housing and duct walls. The scientific literature documents numerous mechanisms that cause flow-induced sound generation, even though not all of them are considered well-understood. Numerical simulation methods are widely used to gather spatially high-resolved insights into physical fields. However, for a centrifugal fan, the numerical simulation of the coupled aero- and vibroacoustic sound emission faces several hurdles, including a tedious meshing procedure, rotating parts, and the disparity of physical scales that need to be resolved for the acoustic field, the flow field, and the mechanical field. This work thus suggests a hybrid workflow to simulate sound generation and the through-wall sound transmission of an enclosed centrifugal fan. The workflow is based on three consecutive simulation runs: 1) a finite-volume-based incompressible CFD simulation to determine the low-Mach-number flow field, 2) a finite-element-based computational aeroacoustic simulation to determine the in-duct sound field, and 3) a finite-element-based vibroacoustic simulation that solves for the direct-coupled mechanic-acoustic simulation to determine the through-wall sound transmission. Additionally, an exemplary simulation of a test fan is conducted and discussed.
CRIS-Team Scopus Importer:2024-07-12

Aktives Turbulenzgitter - Generierung definierter Zuströmturbulenzen für Axialventilatoren - Czwielong, Felix; Becker, Stefan (DAGA 2021 Wien, 2021)

Analytisch und iterativ berechnete Steering-Vektoren zur Lokalisierung rotierender Schallquellen - Ocker, Christof; Herold, Gert; Czwielong, Felix; Pannert, Wolfram (DAGA 2022 Stuttgart, 2022)

Boundary layer measurements of the flow along a streamwise-oriented circular cylinder using particle tracking velocimetry - Näger, Christoph; Wachter, Florian; Lienhart, Hermann; Czwielong, Felix; Riedel, Jörg; Becker, Stefan (International Journal of Heat and Fluid Flow, 2023)
Particle tracking velocimetry (PTV) measurements of an axisymmetric turbulent boundary layer (ATBL) around a long circular cylinder in axial flow were carried out in a large-scale water tunnel at different velocities and at different measurement positions along the cylinder. A relatively thick ATBL developed with ratios of delta/a between 4.6 and 8.1 and a/delta_nu between 313 and 1027, where delta is the boundary layer thickness, delta_nu the viscous length scale and a the cylinder radius. At ratios of delta/a above unity and a/delta_nu above 250, transverse curvature effects are known to influence the boundary layer in the outer region. This was observed in the measured mean velocity profiles as the profiles fall below the planar logarithmic law of the wall. Shape factors close to unity with a rather full velocity profile were determined that explain the relatively high skin friction coefficient known to be present for such ATBL flows. Additionally, measurements of the turbulence intensity and Reynolds stress profiles are presented. The non-intrusive PTV measurement approach allowed to gather near-wall velocity data down to a wall-distance below 10 wall-units. The present study provides valuable information regarding ATBL flows along streamwise-oriented cylinders in the flow regime indicated above by the ranges of delta/a and a/delta_nu . In particular, it fills a gap in the literature as far as experimentally obtained higher-order statistical quantities are concerned, such as root-mean-square velocity fluctuations and Reynolds stresses.<br
Keywords: Axisymetric turbulent boundary layer; Axial cylinder flow; Particle tracking velocimetry; Towed array sonar; Marine seismic streamer; Water tunnel

CONTROLLED INFLOW CONDITIONS FOR RADIAL FANS - AN AEROACOUSTIC RADIAL FAN TEST RIG - Czwielong, Felix; Uffinger, Thomas; Becker, Stefan (15th European Conference on Turbomachinery Fluid Dynamics and Thermodynamics 2023, ETC 2023, 2023)
Radial fans are a common type of machine used in ventilation and air conditioning systems. As well as moving air and creating a pressure increase, the radial turbomachine also emits noise, which is often perceived as disturbing by people in the vicinity. The sound generating mechanisms within the centrifugal blower are complex and often overlapping. As a result, it is difficult to isolate the individual mechanisms. Many of the sound generation mechanisms depend on the inflow to the centrifugal fan, which is usually very inhomogeneous and difficult to control, making it even more difficult to separate the sound mechanisms. In order to better understand the acoustic and fluid mechanical interactions in the centrifugal fan, a new type of dedicated aeroacoustic centrifugal fan test rig has been developed. The test rig can be used to acoustically quiet the inflow of the radial fan and to modify the inflow of the fan. In the future, this will allow a better understanding of the aeroacoustic sound sources of centrifugal fans and their dependence on the flow field. This paper presents the novel test rig and the different inflow conditions. Using an integrated telemetry system, it is possible to determine the pressure fluctuations in the rotating system on the fan blades. This allows a correlation to be made between the inflow conditions, the blade pressures and the far field sound emission. Flow fields with azimuthal, radial and axial velocity gradients were analysed as inflow conditions to the impeller. This distinguishes the test rig from other centrifugal fan test rigs, which usually use undefined inflow conditions from a large chamber. It was found that transient pressure fluctuations in the rotating system at the blade surface could provide new insights into the far-field sound emission of the machine. It was possible to establish a direct link between the flow phenomena at the fan blades and the sound pressure spectra in the far field. The initial investigations confirm the unique investigative capabilities of the novel test rig.
CRIS-Team Scopus Importer:2023-10-13
Keywords: AEROACOUSTIC; INFLOW CONDITIONS; RADIAL FAN; RADIAL FAN TEST RIG; SOUND GENERATION; TELEMETRY

Design of an in-duct micro-perforated panel absorber for axial fan noise attenuation - Floss, Sebastian; Czwielong, Felix; Kaltenbacher, Manfred; Becker, Stefan (Acta Acustica, 2021)
The reduction of fan noise in ducts is a challenging task for acoustic engineers. Usually, the confined space where an absorber can be integrated is small. In addition, one has to consider the influence of the absorber on the flow field and the attenuation of noise should be as great as possible. In this contribution, we investigate the application of a micro-perforated absorber (MPA) in the direct vicinity of a low-pressure axial fan operating at low Mach number conditions. The micro-perforated plates (MPP) are modeled using the Johnson-Champoux-Allard-Lafarge (JCAL) model for porous materials. The entire geometrical setup of duct, fan and MPA is then simulated with the Finite Element (FE) method; the pre-processing effort is reduced by using non-conforming grids to discretize the different regions. The influence of the cavity length and the positioning of the fan are analyzed. The results are then applied to the construction of a full-sized MPA duct component that takes the limited space into consideration. Simulation results and overall functionality are compared to experimental results obtained in an axial-fan test rig. The Finite Element framework proved to be robust in predicting overall sound pressure level reduction in the higher volume flow rates. It is also shown that the MPP increases sound reduction in the low-frequency regime and at two resonant frequencies of the MPA setup. However, its main benefit lies in maintaining the efficiency of the fan. The location of the fan downstream or within the MPA has a significant effect on both the simulated and measured sound reduction.
CRIS-Team WoS Importer:2021-06-04

DESIGN OF LOW DRAG REACTIVE SILENCERS BASED ON THE BOUND STATES IN THE CONTINUUM - Hruška, Viktor; Krpenský, Antonín; Bednařík, Michal; Czwielong, Felix (Proceedings of Forum Acusticum, 2023)
The phenomenon of bound states in the continuum and leaky resonances is employed to design a reactive silencer. It is targeted to prevent a significant spectral line from propagating in a flow-duct while maintaining low pressure drop and installation space (without any lateral extensions). The quasi bound states are achieved by tuning the geometrical parameters of thin plates embedded in a waveguide with dimensions and flow velocities typical for ventilation systems. In general, the procedure works for waveguides with plane wave propagation in the low Mach number regime. An optimization by evolution strategies used for this purpose is described and illustrated on two specific examples.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bound states in the continuum; flow ducts; numerical optimization; reactive silencer

Development of a Didactic Demonstrator for Aeroacoustic Evaluations of Ducts - Schode, Stefan; Boysen, Jan; Mayrhofer, Dominik; Kraxberger, Florian; Heidegger, Patrick; Wurzinger, Andreas; Czwielong, Felix; Maurerlehner, Paul (30th AIAA/CEAS Aeroacoustics Conference, 2024, 2024)
Higher education by means of aeroacoustic laboratories is crucial for the future development of ever quieter and more efficient transportation technologies. The practical training contributes to improving safety, understanding the physical relationships between aerodynamic performance and aeroacoustic noise emission, and provides interdisciplinary training for the next generation of professionals in the field. Hence, this ongoing project adapts an existing aero- and vibroacoustic test rig for low-Mach-number flows in a pipe. It targets the development of a high-quality demonstrator for teaching flow-induced sound generation in ducts. The initial test rig was designed to study flow-induced sound in pipe structures for automotive applications, where low cabin noise is becoming an increasingly important purchase criterion. The test rig comprises a high-pressure/low-Mach-number centrifugal blower, adaptable pipe sections, acoustic absorbers to decouple the test section from blower noise, and an anechoic termination to mitigate acoustic reflections at the pipe exits. Multiple sensors are inserted to track the system operation, flow conditions, internal sound radiation and transmission, and surface vibrations. The highprecision test rig is being transformed into a more transportable and easily accessible teaching tool with the aim of providing optimal conditions for didactic applications.
CRIS-Team Scopus Importer:2024-09-13

Development of a test rig for the investigation of flow-induced mechanisms of sound generation at radial fans - Uffinger, Thomas; Czwielong, Felix; Renz, Andreas; Heidegger, Patrick; Schoder, Stefan; Kaltenbacher, Manfred; Becker, Stefan (Applied Acoustics, 2023)
A low sound pressure level is a crucial quality feature for industrial and non-industrial radial fans. The scientific literature documents numerous mechanisms of flow-induced sound generation that can occur in a radial fan. Nevertheless, not all sound generation mechanisms are considered well-understood today and thus are still dealt with in ongoing research. This work develops an experimental setup to investigate the different mechanisms of flow-induced sound generation in radial fans. The aim is to close the existing gap between available experimental research on axial and radial fans. One critical factor for the experimental investigation of flow-induced sound generation in fans is the control of inflow. Due to the design of radial fans, the fluid flow deflects from the axial supply duct to the radial direction upstream of the impeller, generating a complex flow field with limited control possibilities. Hence, we designed a test rig that improves the control of inflow conditions, aiming to resolve the superposed sound generation mechanisms in acoustic measurements. This paper presents the key features of the test rig and some first experimental results. The investigation of the distinct sound generation mechanisms is left to future work based on the introduced test rig.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Aeroacoustics; Experimental investigations; Flow-induced sound; Radial fans; Test rig development; Turbomachinery

Eigengeräuschmessung eines Quadrokopters (UAV) im Flug mit dem Fokus auf Datenerfassung, Mikrofonposition und Mikrofonwindschutz - Benz, Julian; Czwielong, Felix; Gründer, Andreas; Franke, Jörg; Becker, Stefan (DAGA 2024, 2024)
Keywords: Drohne; Quadrokopter; Eigengeräusch; Multikopter; Mikrofon; Mikrofonwindschutz

Experimental Investigation of the Impact of 3D-Metal-Printed Perforated Leading Edges on Airfoil and Axial Fan Noise - Ocker, Christof; Pannert, Wolfram; Merkel, Markus; Geyer, Thomas; Czwielong, Felix; Krömer, Florian; Becker, Stefan (AIAA AVIATION 2020 FORUM, 2020)
An experimental investigation of the aerodynamic performance and noise emission of airfoils and fan blades with perforated leading edges is presented. In a first step, a detailed wind tunnel study was carried out. Therefore, measurements on sixteen airfoils with different leading edge designs were performed for various flow speeds and geometric angles of attack. The airfoils with perforated leading edges were made of an aluminum alloy using a powder bed fusion based additive manufacturing process. For the measurements, two turbulence grids were used to generate different inflow turbulence conditions. The aerodynamic performance was captured with a wind tunnel balance and the acoustic measurements were performed using a planar microphone array. Based on the results from that study, unskewed fan blades with four different perforated leading edge designs were manufactured in a second step. With the aim of reducing turbulence ingestion noise of axial fans, the axial fans were examined with regard to their aerodynamics, total-to-static efficiency and sound emissions under free inflow and grid-generated turbulent inflow conditions. The investigations on airfoils and fan blades with perforated leading edge show a notable frequency-dependent noise reduction, but also a loss of aerodynamic performance.<br
Keywords: Axialventilator; Tragflügel; 3D-Druck; poröses Material; Vorderkante; Turbulenz

Experimental investigation of the influence of different leading edge modifications on the sound emission of axial fans downstream of a heat exchanger - Czwielong, Felix; Krömer, Florian; Paruchuri, Chaitanya; Becker, Stefan (Proceedings of the 23rd International Congress on Acoustics, integrating 4th EAA Euroregio 2019, 2019)
Axial fans have a major impact on the sound emission of technical systems. One of the common applications of low-pressure axial fans is their usage in air conditioning and cooling circuits. In most cases the fan operates downstream of a heat exchanger in this scheme. The suction side heat exchanger changes the upstream flow field of the fan, often resulting in an increase in the sound pressure level of the axial fan compared to undisturbed inflow conditions. Investigations on sound radiation of aerorfoils showed that leading-edge modifications like serrations or slits reduce the turbulence-aerofoil interaction noise. In this study, the impact of two different leading-edge modifications (sinusoidal and slit) on the sound emissions of a forward skewed low-pressure axial fan was examined. The inflow conditions varied between a free inflow and a disturbed inflow, generated by a heat exchanger located on the suction side of the axial fan. The results show that the modification of the leading edge has a positive influence on the sound radiation of the axial fan for both inlet conditions discussed above.<br
Keywords: Axialventilator; Vorderkante; Serrations; Slits; Wärmeübertrager

Experimental Investigation of the Sound Emission of Skewed Axial Fans with Leading-Edge Serrations - Krömer, Florian; Czwielong, Felix; Becker, Stefan (AIAA Journal, 2019)
Axial fans represent a major source of noise in technical systems. Based on investigations on airfoils, a promising measure for reducing the sound emission of such systems with axial fans is the application of leading-edge serrations to the fan blade. Hence in this study, the joint impact of fan-blade skew—as a commonly used noise-reduction approach—and leading-edge serrations on the sound emission of low-speed axial fans was investigated. Forward-, backward-,and unskewed fans with five different leading-edge modifications were used. For each fan, a reference configuration with straight leading edges and four configurations with sinusoidal leading-edge serrations (with two different amplitude values and two different wavelength values) were examined. The results show that, among the reference fans with unmodified leading edges, the forward-skewed fan had the lowest sound emission. The serrations applied to the unskewed fan lead to an increase in the efficiency and a decrease in the sound emission. When applied in combination with fan-blade skew, the serrated fans showed an even lower sound emission and a higher efficiency— even the forward-skewed fan, which already has a low sound emission without any leading-edge modifications. The highest sound reduction was achieved by applying the serrations with the smallest wavelength and the highest amplitude. The findings prove that even for low-noise fans with forward-skewed fan blades, a further sound reduction is possible with the use of leading-edge serrations.<br
Keywords: axial fan; leading edge; serrations; sound reduction; spectra; acoustic; aerodynamic

Experimental investigation of the sound emission of skewed axial fans with leading-edge-serrations - Krömer, Florian; Czwielong, Felix; Becker, Stefan (25th AIAA/CEAS Aeroacoustics Conference, 2019)
Axial fans represent a major source of noise in technical systems. Based on investigations on airfoils, a promising measure for reducing the sound emission of such systems with axial fans is the application of leading-edge serrations to the fan blade. Hence in this study, the joint impact of fan-blade skew – as a commonly used noise-reduction approach – and leading-edge serrations on the sound emission of low-speed axial fans was investigated. Forward-, backwardand unskewed fans with five different leading-edge modifications were used. For each fan, a reference configuration with straight leading edges and four configurations with sinusoidal leading-edge serrations (with two different amplitude values and two different wavelength values) were examined. The results show that among the reference fans with unmodified leading edges, the forwardskewed fan had the lowest sound emission. The serrations applied to the unskewed fan lead to an increase in the efficiency and a decrease in the sound emission. When applied in combination with fan-blade skew, the serrated fans showed an even lower sound emission and a higher efficiency – even the forward-skewed fan, which already has a low sound emission without any leading-edge modifications. The highest sound reduction was achieved by applying the serrations with the smallest wavelength and the highest amplitude. The findings prove that even for low-noise fans with forward-skewed fan blades, a further sound reduction is possible with the use of leading-edge serrations.<br
Keywords: Vorderkante; Axialventilator; Zacken; Akustik

Experimental investigations of the sound emissons of axial fans under the influence of suction-side heat exchangers - Czwielong, Felix; Krömer, Florian; Becker, Stefan (25th AIAA/CEAS Aeroacoustics Conference, 2019)
A primary application of axial fans is their use in combination with heat exchangers in air conditioning systems. In addition to the positive aspect of cooling, air conditioning systems generate noise. The noise generation mechanisms of axial fans with suction-side heat exchangers are not yet fully understood, in particular due to a lack of investigations on real systems. In this study, we investigate the flow field and the acoustic interactions between axial fans and suction-side heat exchangers of real air conditioning systems. As a result, we have found that the geometry of the heat exchangers affects the flow field upstream of the axial fans with respect to the anisotropy of the flow. The heat exchangers influenced the flow field similar to flow straighteners. In addition, we showed that the choice of heat exchangers and fan blade skew type changed the acoustics of air conditioning systems. Our results demonstrate that the acoustic optimization of air conditioning systems can only be achieved through the joint optimization of heat exchangers and axial fans. Although not all parameters were examined, we were able to show the influence of the heat exchangers on the flow field and the acoustic radiation of the axial fans. Further investigations on the acoustic interaction between heat exchanger and axial fan would contribute to the systematic optimization of air conditioning systems.<br
Keywords: Wärmeübertrager; Akustik; Axialventilator; Turbulenz

Experimentelle Untersuchung der Schallabstrahlung von Wärmeübertrager-Axialventilator-Modulen - Czwielong, Felix; Krömer, Florian; Becker, Stefan (Fortschritte der Akustik - DAGA 2019 45. Deutsche Jahrestagung für Akustik, 18.-21. März 2019 in Rostock, 2019)
Eine Hauptanwendung von Axialventilatoren ist ihr Einsatz in Kombination mit saugseitigen Wärmeübertragern in Klimatisierungs- und Belüftungssystemen. Die Akustik solcher Anlagen wird hauptsächlich durch die eingesetzten Axialventilatoren und Wärmeübertrager bestimmt. Dabei stellen die Schaufelblattgeometrie und die Zuströmbedingungen wesentliche Einflussparameter auf die Schallabstrahlung dar. Bisherige Untersuchungen zeigten, dass Zuströmbedingungen mit erhöhtem Turbulenzgrad eine Verstärkung der Schallabstrahlung induzieren. Zudem variieren die Auswirkungen der gestörten Einströmbedingungen je nach Schaufelblattgeometrie. In realen Klimasystemen sind die Wechselwirkungen zwischen dem Axialventilator und den Zuströmbedingungen, welche von dem Wärmeübertrager erzeugt werden, noch nicht vollständig untersucht und verstanden worden. Um den Einfluss von Wärmeübertragern auf die Schallabstrahlung von Axialventilatoren zu bestimmen, wurden verschiedene Wärmeübertrager mit unterschiedlichen Lamellentypen untersucht. Als Referenzfall diente ein leeres Wärmeübertragergehäuse ohne Kühllamellen. Zunächst wurde das Strömungsfeld stromabwärts der Wärmeübertrager bestimmt. Der Einfluss der induzierten Zuströmbedingungen auf die Akustik von Axialventilatoren wurde an unterschiedlich gesichelten Ventilatoren (vorwärts-, rückwärts- und ungesichelt) untersucht. Die Ergebnisse zeigen, dass der Turbulenzgrad stromabwärts der Wärmeübertrager je nach Lamellentyp ansteigt oder verringert wird. Der Einfluss der variierten Zuströmbedingungen auf die Akustik zeigte sich vor allem bei hohen Volumenströmen. Die Sichelung der Ventilatorschaufeln stellte sich dabei als wesentlicher Einflussfaktor auf die Schallabstrahlung von Axialventilatoren mit saugseitigen Wärmeübertragern heraus.<br
Keywords: Axialventilatoren; Wärmeübertrager; Akustik; Schallabstrahlung

IMPACT OF HEAT EXCHANGERS ON AXIAL FAN ROTOR NOISE IN HEAT PUMP APPLICATIONS - Czwielong, Felix; Becker, Stefan (Proceedings of Forum Acusticum, 2023)
Due to installation effects, heat exchangers can increase the sound radiation of axial fans in heat pump applications. The increase in rotor noise is due to the disturbed flow field induced by the heat exchanger. In particular, the diameter of the coolant tube and the geometry of the heat exchanger have a major influence on the resulting sound radiation of the axial fan. Inhomogeneities in the flow field caused by the geometry of the heat exchanger housing have a significant influence on the tonal components in the fan's sound pressure spectrum. As the turbulence level increases, the broadband sound radiation of the fan increases due to the amplification of the leading edge sound sources. The tonalities in the radiated sound field and the total sound pressure level could be reduced in the future by appropriate selection of the heat exchanger parameters. This will allow the installation of quieter heat pumps in residential areas and thus increase the acceptance of the units by the public.
CRIS-Team Scopus Importer:2024-12-16
Keywords: axial fans; distrubed inflow; heat exchanger; heat pumps; rotor noise

Influence of a micro-perforated duct absorber on sound emission and performance of axial fans - Czwielong, Felix; Floss, Sebastian; Kaltenbacher, Manfred; Becker, Stefan (Applied Acoustics, 2020)
In this article we investigate the influence of varying flow conditions on the acoustic behaviour of a micro-perforated panel absorber (MPA), applied in the vicinity of an axial fan. The predesign of the MPA was conducted by using the Finite Element Method (FE) in combination with porous material modelling approaches. Experimental results of emitted sound spectra and fan characteristic of different fan blade geometries, positioning of the fan to the absorber, as well as changes in turbulent intensity are presented. The studies showed that the investigated MPA duct reduces the overall sound pressure level emitted by the fan by up to 16 dB while maintaining the same efficiency and pressure build-up. From an acoustic and aerodynamic point of view, it was more efficient if the fan operate downstream of the MPA instead of within the MPA. This arrangement increased the efficiency and avoided high-frequency sound generation, which is caused by the flow through the MPA. The results show that the function of the MPA can be used for different fan geometries and that inlet turbulence improves the properties of the absorber.<br
Keywords: Axial fans Micro-perforated plate absorber Duct modifications Noise attenuation Overflowed sound absorbers Design optimization

INFLUENCE OF CHORD LENGTH AND LOAD DISTRIBUTION MODIFICATION ON THE SOUND EMISSION AND EFFICIENCY OF A BENCHMARK FAN - Benz, Julian; Czwielong, Felix; Renz, Andreas; Ocker, Christof; Sedlmajer, Michael; Merkel, Markus; Schoder, Stefan; Becker, Stefan (Proceedings of Forum Acusticum, 2023)
The design parameters of axial fans, such as load distribution over the blade, chord length and the angle of attack, significantly influence the resulting aerodynamic and aeroacoustic properties of the fans. Based on an international benchmark fan, its design parameters were modified and two additional fans were created. In the process, all three fans had the same specific load, but in one case the chord length of the fan was varied and in the second case an additionally modified load distribution was applied. The modified load distribution is based on Prandtl's idea that a bell-shaped load distribution has the lowest induced drag on aircraft wings by reducing the wing tip vortex. The numerical investigations demonstrated that this reduction can be also achieved on axial fans leading to increased aerodynamic efficiency. By using the Lighthill analogy, a decrease in the sound emission of the fan could be found. In addition, the modification with the increased chord length exhibits improved aerodynamic and acoustic properties compared to the benchmark fan.
CRIS-Team Scopus Importer:2024-12-16
Keywords: axial fan; CAA; CFD; chord length; load distribution

Installationseffekte von Wärmeübertragern auf Axialventilatoren - Czwielong, Felix; Hruška, Viktor; Mader, Tobias; Becker, Stefan (DAGA 2022 Stuttgart, 2022)

MACHINE-LEARNING CLUSTERING METHODS APPLIED TO DETECTION OF NOISE SOURCES IN LOW-SPEED AXIAL FAN - Tieghi, Lorenzo; Becker, Stefan; Corsini, Alessandro; Delibra, Giovanni; Schoder, Stefan; Czwielong, Felix (Proceedings of the ASME Turbo Expo, 2022)
The integration of rotating machineries in human-populated environments requires to limit noise emissions, with multiple aspects impacting on control of amplitude and frequency of the acoustic signature. This is a key issue to address and when combined with compliance of minimum efficiency grades, further complicates the design of axial fans. The aim of this research is to assess the capability of unsupervised learning techniques in unveiling the mechanisms that concur to the sound generation process in axial fans starting from high-fidelity simulations. To this aim, a numerical dataset was generated by means of LES simulation of a low-speed axial fan. The data set is enriched with sound source computed solving a-posteriori the perturbed convective wave equation (PCWE). First, the instantaneous flow features are associated to the sound sources through correlation matrices and then projected on latent basis to highlight the features with the highest importance. This analysis in also carried out on a reduced dataset, derived by considering two surfaces at 50% and 95% of the blade span. The sampled features on the surfaces are then exploited to train three cluster algorithms based on partitional, density and Gaussian criteria. The cluster algorithms are optimized and their results are compared, with the Gaussian Mixture one demonstrating the highest similarity (>80%). The derived clusters are analyzed, and the role of statistical distribution of velocity and pressure gradients is underlined. This suggests that design choices that affect these aspects may be beneficial to control the generation of noise sources.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Aeroacoustics; Gaussian Mixture; Machine-learning

Machine-Learning Clustering Methods Applied to Detection of Noise Sources in Low-Speed Axial Fan - Tieghi, Lorenzo; Becker, Stefan; Corsini, Alessandro; Delibra, Giovanni; Schoder, Stefan; Czwielong, Felix (Journal of Engineering For Gas Turbines and Power-Transactions of the Asme, 2023)
The integration of rotating machineries in human-populated environments requires to limit noise emissions, with multiple aspects impacting on control of amplitude and frequency of the acoustic signature. This is a key issue to address and when combined with compliance of minimum efficiency grades, further complicates the design of axial fans. The aim of this research is to assess the capability of unsupervised learning techniques in unveiling the mechanisms that concur to the sound generation process in axial fans starting from high-fidelity simulations. To this aim, a numerical dataset was generated by means of large Eddy simulation (LES) simulation of a low-speed axial fan. The dataset is enriched with sound source computed solving a-posteriori the perturbed convective wave equation (PCWE). First, the instantaneous flow features are associated with the sound sources through correlation matrices and then projected on latent basis to highlight the features with the highest importance. This analysis in also carried out on a reduced dataset, derived by considering two surfaces at 50% and 95% of the blade span. The sampled features on the surfaces are then exploited to train three cluster algorithms based on partitional, density and Gaussian criteria. The cluster algorithms are optimized and their results are compared, with the Gaussian Mixture one demonstrating the highest similarity (> 80%). The derived clusters are analyzed, and the role of statistical distribution of velocity and pressure gradients is underlined. This suggests that design choices that affect these aspects may be beneficial to control the generation of noise sources.
CRIS-Team WoS Importer:2023-03-31

Metal-3D-printed permeable leading edges for airfoil noise reduction - Ocker, Christof; Geyer, Thomas F.; Czwielong, Felix; Becker, Stefan; Merkel, Markus (Quality Analysis of Additively Manufactured Metals, 2022)
Additive manufacturing offers many possibilities compared to conventional manufacturing methods, which makes it a very promising tool for industry sections like aerospace or energy due to the high accuracy, structural stability, and the possibility to integrate additional functionalities into complex parts and assemblies. One example includes the rotor and/or stator blades of turbomachinery, which can be modified in order to reduce the generation of aerodynamic noise using permeable, Metal-3D-printed structures integrated into the blade leading edge. An experimental study of the aerodynamic and the aeroacoustic performance of airfoils with additive manufactured permeable leading edges under disturbed inflow conditions is presented. A turbulent inflow increases the noise emission of the airfoils, which is related to turbulence interaction noise. By integrating a permeable structure on the leading edge of the airfoils, the noise emission can be reduced. However, these modifications may reduce the aerodynamic performance of the airfoil. For the identification of quiet and aerodynamically effective leading-edge modifications, high dimensional accuracy of the geometrically thin structures is required. Therefore, the geometry of the manufactured airfoils with integrated leading-edge modification was measured with computer tomography and compared to the computer-aided design model. Then, wind tunnel measurements were conducted to identify the aerodynamic and aeroacoustic performance of the airfoils.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Airfoil; Dimensional accuracy; Noise reduction; Permeable leading edge

Micro-perforated panels for noise reduction - Floss, Sebastian; Czwielong, Felix; Becker, Stefan; Kaltenbacher, Manfred (Elektrotechnik und Informationstechnik, 2021)
Space limitations in duct applications, new industrial and health safety regulations require new absorber configurations. Micro-perforated panels (MPP) as used in micro-perforated absorbers (MPA) allow new sound absorber concepts in the category of metamaterials. In this contribution we investigate MPA designs for the low and mid-to-high frequency range and apply finite element (FE) simulations to precisely design absorber configurations for applications in room acoustics and axial fans. The investigations show that the MPA’s cavity configuration must be customized for the desired frequency range and has significant influence on fan performance when applied in a duct flow setu
Keywords: MPP; MPA; Metamaterial; finite Elemente; Kanalakustik; Axialventilator

Micro-perforated panels in interaction with boundary layers in zero pressure gradient flow - Floss, Sebastian; Czwielong, Felix; Becker, Stefan; Kaltenbacher, Manfred (DAGA 2021 Wien, 2021)

Novel design for acoustic silencers for ducts with flow based on the bound states in the continuum - Hruška, Viktor; Krpenský, Antonín; Bednar̆ík, Michal; Czwielong, Felix (Archive of Applied Mechanics, 2023)
The concept of bound states in the continuum and leaky resonances is utilized in the design of a reactive silencer that can effectively suppress significant spectral lines while maintaining a low-pressure drop within the flow duct and does not require additional installation space. By adjusting the geometrical parameters of thin plates that are embedded in a waveguide, quasi-bound states (or leaky resonances) can be achieved. An optimization algorithm is employed to fine-tune these parameters, and this process is illustrated through two specific examples. The resulting design is validated through numerical simulations that account for the effects of low Mach number flow. The investigations showed that it is possible to design a spectral silencer with low-pressure drop based on the chosen approach. By combining several leaky resonances, stopbands were created with a transmission loss of up to 17 dB in a frequency range of 10 Hz.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Axial fans; Blade passing frequency; Bound states in the continuum; Ducts with flow; Leaky resonances; Reactive silencers

Numerical flow noise simulation of an axial fan with a Lattice-Boltzmann solver - Antoniou, Evangelos; Romani, Gianluca; Jantzen, Andreas; Czwielong, Felix; Schoder, Stefan (Acta Acustica, 2023)
In this paper, a transient and compressible solver based on the Lattice-Boltzmann Method/Very Large Eddy Simulation (LBM/VLES) approach is employed to predict unsteady flow physics and flow-induced noise generation of a low-pressure axial fan. Aerodynamic and aeroacoustic measurements provided by the European Acoustics Association (EAA) benchmark platform are used for validation purposes. Boundary and design operating conditions are applied to the numerical model to replicate the experimental setup. Simulation and experimental data are compared, showing an excellent agreement in terms of fan efficiency with less than 1% deviation, as well as broadband and tonal noise within 0.7 dBA in terms of overall sound pressure level. An advanced post-processing analysis is performed to shed light on the noise generation mechanism in tip clearance. It is observed that both fine random turbulent structures and large coherent vortices are generated in the tip gap. The continuous impingement of the fine turbulence with the following blades and the blade itself is responsible for the radiation of broadband noise, while the interaction between the large coherent tip vortices, spinning at a lower angular velocity with respect to the fan shaft, and the following blades leads to the generation of narraowband peaks at sub-harmonics of the blade-passing frequencies. Finally, a beamforming analysis further confirms that the main noise sources are located in the blade tip clearance and tip regions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aeroacoustics; Axial fans; Computational Fluid Dynamics; Lattice-Boltzmann Method; Sub-harmonic noise

On the acoustic effects of sonic crystals in heat exchanger arrangements - Czwielong, Felix; Hruška, Viktor; Bednařík, Michal; Becker, Stefan (Applied Acoustics, 2021)
Heat exchangers can be found in a large number of technical systems and installations. They are usually operated in combination with other machines, such as axial fans, in order to remove or supply heat to a system. The heat exchanger can influence the existing flow field and thus lead to increased noise emission from fans located downstream of the heat exchanger. This can be observed, for example, in air conditioning units in which axial fans operate in combination with heat exchangers. Even though this mechanism is known, it is not yet understood how the heat exchanger affects the sound propagation of the sound produced by the downstream machine. For example, the heat exchanger may lead to a change in directional characteristics or specific frequencies may be attenuated. In order to better understand the interaction of the heat exchanger with the sound field, sound power measurements were carried out on various heat exchangers and the sound propagation was simulated numerically. It was shown that the sound attenuation due to the interaction with the periodic tube array is detectable in heat exchangers and that this leads to a sound reduction at the Bragg frequency. Based on its filling factor, the heat exchanger can reduce the sound propagation in certain frequency bands by up to 10 dB if the geometrirical properties are selected suitably. The simulations of a single unit cell confirm in very good agreement with the experimental results. This allows the conclusion that the approach presented in this paper is a cost-effective way to model acoustic effects of heat exchangers. Furthermore, sound attenuation effects by the heat exchanger were caused by thermoviscous effects on the cooling fins and dimensions of the heat exchanger housing.
Keywords: Heat exchangers; Sonic crystals; Sound propagation; Axial fans; Bragg frequency; Sound power measurements

ON THE AEROACOUSTIC PROPERTIES OF A PRANDTL-FAN - Czwielong, Felix; Benz, Julian; Ocker, Christof; Renz, Andreas; Sedlmajer, Michael; Merkel, Markus; Becker, Stefan (Proceedings of the ASME Turbo Expo, 2023)
Axial fans are used in many machines and equipment in close proximity to people. Therefore, acoustic optimization of the fans is essential to protect the well-being of people and to ensure a quiet environment. The sound emission of fans is determined, among other factors, by the selected load distribution of the blades and the resulting angles of attack and chord lengths. A bell-shaped load distribution developed by Prandtl in 1933 was applied to a benchmark fan and investigated aeroacoustically. A total of three axial fans were numerically simulated for flow and acoustics at the design point. One of these fans is an international benchmark fan, the second is a fan with the same isoenergetic load distribution but a different chord length, and the third fan has the Prandtl load distribution and the same modified chord length. Based on the simulations performed, it was shown that a larger chord length leads to an improvement in the aerodynamic and acoustic properties of the axial fan with isoenergetic load distribution. This is due to the reduced blade tip overflow and the associated reduced pressure fluctuations at the blade surface. The bell-shaped load distribution increases the efficiency of the fan, but also increases the total sound emission by 1.5 dB compared to the axial fan with constant chord length and isoenergetic load distribution. This is due to the increased interaction between the blades, as the blade tip vortex hits the following blade leading edge more frontally. This increase occurs despite a reduction in the strength of the blade tip vortex. Compared to the benchmark fan, the changes in chord length and Prandtl’s load distribution resulted in a sound reduction of 3.9 dB and an increase in efficiency of 4%. It was shown that the modifications can be used for future aeroacoustic optimization of axial fans.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Aeroacoustics; Axial fan; CFD; Chord length; Lighthill; Load; Prandtl-Fan

On the interactions of the induced flow field of heat exchangers with axial fans - Czwielong, Felix; Soldat, Julia; Becker, Stefan (Experimental Thermal and Fluid Science, 2022)
In a large number of applications, heat exchanger modules consist of a combination of a heat exchanger and a turbomachinery. An axial fan is often used as the turbomachine in these scenarios. These modules are part of the daily life of people and are located in the direct vicinity of them. The interaction of the flow field with the heat exchanger generates disturbed inflow conditions upstream of the axial fan, which are characterized by increased turbulence properties. These disturbed inflow conditions often lead to increased sound radiation from the fan. In this study, the flow field of eight different heat exchangers was characterized and the effects on the sound emissions of the axial fan were analyzed. The main focus was on the geometry of the heat exchanger. By means of smoke visualization, the formation of significant turbulence points in the flow field of heat exchangers could be demonstrated. The spots with increased turbulence intensities are induced by the geometry transition from rectangular to round between the heat exchanger and the duct of the axial fan. It was found that a round geometry of the heat exchanger leads to a more homogeneous flow field and thereby reduces the sound emissions of the axial fan. Also a increase of the flow through area of the heat exchanger brings benefits for the acoustics of the axial fan. Especially the tonal components of the blade passing frequency of the fan were strongly dependent on the chosen heat exchanger. The tonal components could be reduced if the homogeneity of the flow field was increased by a round heat exchanger geometry.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Axial fan; Heat exchanger; Inflow turbulence; Radiator; Sound emissions; Turbulence ingestion noise

Optimierte Schallreduktion in Axialventilatorsystemen durch mikroperforierte Absorber - Czwielong, Felix; Floss, Sebastian; Kaltenbacher, Manfred; Becker, Stefan (DAGA 2020 Hannover, 2020)
Keywords: MPP; MPA; Absorber; Schallreduktion; Rohrsystem; Axalventilator; Mikroperforation

Permeable Leading Edges for Airfoil and Fan Noise Reduction in Disturbed Inflow - Ocker, Christof; Geyer, Thomas; Czwielong, Felix; Krömer, Florian; Pannert, Wolfram; Merkel, Markus; Becker, Stefan (AIAA Journal, 2021)
A detailed experimental study on the aerodynamic performance and noise emission of airfoils and fan blades with permeable leading edges under disturbed inflow conditions was performed. The airfoils and fan blades with permeable leading edges were made of an aluminum alloy using a powder bed fusion-based additive manufacturing process. In a first step, a wind-tunnel study was carried out. This consisted of detailed aerodynamic and aeroacoustic measurements on 16 airfoils with different permeable leading-edge designs that were performed for various flow speeds and geometric angles of attack. Based on the results from that study, unskewed fan blades with four different permeable leading-edge designs were manufactured in a second step. With the aim of reducing turbulence interaction noise of axial fans, the fans were examined with regard to their aerodynamic and acoustic properties under grid-generated turbulent inflow conditions. In a third step, a possible transfer of the observed noise emission from airfoils with permeable leading edge to that of fan blades was investigated. It was found that a notable broadband noise reduction can be transferred from airfoil applications to the sound spectra of axial fans. At the same time, the porous modifications can reduce the aerodynamic performance, and hence the fan efficienc
Keywords: Axial fan; Leading edge; porosity; sound reduction; airfoil; acoustics; fluid dynamics

Permeable Structures for Leading Edge Noise Reduction - Ocker, Christof; Czwielong, Felix; Geyer, Thomas; Paruchuri, Chaitanya; Merkel, Markus; Becker, Stefan (AIAA AVIATION 2021 FORUM, 2021)
An experimental investigation on the acoustic and aerodynamic effect of permeable structures at airfoils and fan blades under distorted inflow conditions was performed. The study focuses on the position and the extent of the porous structure with respect to the leading edge. In a first step, aerodynamic and aeroacoustic measurements are carried out in an aeroacoustic wind tunnel on a large number of airfoils for various wind speeds and angles of attack. The airfoils were made of an aluminum alloy using a powder bed fusion based additive manufacturing process. The permeable structure is located either directly at the leading edge or at a short distance downstream of the leading edge with an extent of 5 %, 10 %, and 15 % of the total chord length. Based on the results from the wind tunnel measurements, unskewed fan blades with four different permeable leading edge designs were constructed in a second step. The axial fan measurements were examined with regard to their aerodynamic and acoustic properties under grid-generated turbulent inflow conditions. First, the axial fan performances are compared at the same rotational speed and then at varying rotational speeds to obtain the same total-to-static pressure rise. It was observed for both, airfoil and fan blades, that a permeable structure downstream from the leading edge improves the aerodynamics and the noise reduction in comparison to a permeable structure directly at the leading edge.

Revisiting the EAA Benchmark for a low-pressure axial fan - Schoder, Stefan; Czwielong, Felix; Kaltenbacher, Manfred (DAGA 2022 Stuttgart, 2022)

Schallquellenlokalisierung an geschlitzten Axialventilatoren mit rotierendem Beamforming - Ocker, Christof; Czwielong, Felix; Krömer, Florian; Paruchuri, Chaitanya; Pannert, Wolfram; Becker, Stefan (DAGA 2021 Wien, 2021)

Sensibilitätsanalyse verschiedener Wärmeübertragerparameter und deren Einfluss auf die Schallabstrahlung von Axialventilatoren - Czwielong, Felix; Becker, Stefan (DAGA 2020 Hannover, 2020)
Keywords: Wärmeübertrager; Axialventilatoren; Sensibilität; Akustik; Strömungsmechanik

Silencers in Flow Ducts using Double-Layer MPA - Berchtenbreiter, Benedikt; Grützner, Dominik; Czwielong, Felix; Becker, Stefan (30th AIAA/CEAS Aeroacoustics Conference, 2024, 2024)
Microperforated absorbers (MPA) are an established technology for the attenuation of sound in flow-carrying ducts. MPAs usually consist of a microperforated panel (MPP) in combination with a back volume. The damping maxima of MPAs occur in the range of their resonant frequencies and the effect is narrowband compared to passive porous or fibrous absorbers, which damp broadband at high frequencies. The resonant frequencies of MPAs decrease with increasing back volume. To reduce the required back volume, a double-layer MPAs with an additively manufactured porous absorber underneath the MPP as an acoustic metamaterial are introduced. The advantage of using additively manufactured absorbers over conventional absorbers is that the acoustic properties can be specifically adapted to the required impedance boundary conditions. The reflection, transmission and dissipation of the investigated mesh structures correspond to the characteristics of porous absorbers. The effective fluid properties of the individual grating structures were successfully determined using the admittance matrix of the structures. With the possibility of modelling the grids as an effective fluid, a design of the double-layer MPA was obtained. The results show that the additively manufactured absorbers reduce the required back volume by up to 13% in comparison to a single layer version. Finally, measurements were carried out with channel flow at Mach numbers up to 0.1. The sound-attenuating effects of both single-and double-layer MPAs were changed in the frequency and amplitude depending on the flow velocity parameters.
CRIS-Team Scopus Importer:2024-09-06

Simulating the Fluid-Structure-Acoustic Interaction of the Confined Flow in a Centrifugal Fan - Heidegger, Patrick; Czwielong, Felix; Becker, Stefan; Kaltenbacher, Manfred (15th International Conference on Theoretical Computational Acoustics, ICTCA 2023, 2023)
CRIS-Team Scopus Importer:2024-12-16
Keywords: centrifugal fan; computational aeroacoustics; computational fluid dynamics; confined flow; finite element method; ICTCA 2023; PCWE

Simulating Wind Noise with Airflow Speed-Dependent Characteristics - Mirabilii, Daniele; Lodermeyer, Alexander; Czwielong, Felix; Becker, Stefan; Habets, Emanuël (International Workshop on Acoustic Signal Enhancement, IWAENC 2022 - Proceedings, 2022)
Generating noise samples is crucial in developing and testing noise reduction algorithms or training deep learning models. This work proposes a wind noise generation model with airflow speed-dependent features. A linear predictive analysis of wind noise measured in a wind tunnel at different flow velocities was carried out. This analysis showed that temporal and spectral features depend on the flow speed. The prediction residual's statistics and the filter coefficients are first extracted and then modeled based on the flow speed. The obtained models are then combined to synthetically generate wind noise given a time-varying flow speed profile as input, in contrast to an existing framework where temporal and spectral features were assumed speed-invariant. A subjective evaluation is carried out to assess the perceptual authenticity of the generated noise compared to the existing method.
CRIS-Team Scopus Importer:2022-11-25
Keywords: analysis; synthesis; Wind noise

Sound Emissions of Axial Fans with Leading-Edge Serrations on different spanwise Locations - Czwielong, Felix; Krömer, Florian; Becker, Stefan (PROCEEDINGS OF INTERNOISE 2019 The 49th International Congress and Exhibition on Noise Control Engineering, 2019)
Axial fans are used in a variety of technical systems such as air conditioners, trains, cars and ventilation systems. In these systems, axial fans are a dominant source of noise. Based on the investigations of flat-plate fans and airfoils, it has been found that serrated leading edges reduce the sound radiation compared with a straight leading edge. In this study, the sound emission of axial fans with leading-edge serrations, applied to dierent spanwise locations of the fan blade, was investigated. For that three fans with different leading-edge configurations (fully serrated, serrations on the outer 2/3 and 1/3 of the fan blade) and a reference fan without serration were examined experimentally. The results showed that leading-edge serrations influence the sound emissions of the axial fans. For high volume flow rates, the serrations led to a reduction of the sound radiation - the fan with serrations on the full span showed the highest sound reduction. For low volume flow rates, the sound emission was increased with the leading-edge serrations.<br
Keywords: Axialventilator; Vorderkante; Schallenstehung; Schallreduktion; Modifkation

Sound reduction in heat exchanger modules by integrating plate absorbers with sub-millimeter openings - Czwielong, Felix; Floss, Sebastian; Kaltenbacher, Manfred; Becker, Stefan (Acta Acustica, 2021)
In air conditioning systems heat exchangers are frequently installed upstream of ventilators. These modules are part of the daily life of humans and should therefore create an environment that is as quiet as possible. The heat exchanger generates increased turbulence, which leads to increased sound emissions of the ventilator. Due to installation space limitations, it is not possible to connect silencers to the heat exchanger module. A novel concept is presented, which allows to reduce the sound emissions of heat exchanger due to plate absorbers without the need of additional installation room. The plates contain sub-millimeter openings. They are integrated into the heat exchanger housing together with back volumes. This arrangement guarantees compactness and generates no additional flow resistance. The emitted sound could be reduced by up to 2.9 dB in the partial load range. The main advantages of the concept presented are individual adjustment, cost-effective design and simple installatio
Keywords: MPP; Heat exchanger; MPA; Axial fan; Sound reduction

Strukturierte Porosittät zur Lärmminderung von Axialventilatoren - Ocker, Christof; Czwielong, Felix; Geyer, Thomas; Merkel, Markus; Becker, Stefan (DAGA 2021 Wien, 2021)

The influence of periodic structures on sound propagation through heat exchangers - Czwielong, Felix; Hruška, Viktor; Bednařík, Michal; Becker, Stefan (DAGA 2021 Wien, 2021)

Untersuchung der Schallabstrahlung von gesichelten Axialventilatoren mit sinusförmigen Vorderkanten - Becker, Stefan; Czwielong, Felix; Krömer, Florian (Fortschritte der Akustik - DAGA 2019 45. Deutsche Jahrestagung für Akustik, 18.-21. März 2019 in Rostock, 2019)
Die Schallabstrahlung von Axialventilatoren wird maßgeblich von der Geometrie der Laufradschaufel und den Einströmrandbedingungen bestimmt. Insbesondere bei einer Zuströmung mit hohen Turbulenzgraden ist eine verstärkte Schallabstrahlung zu erwarten. Basierend auf Untersuchungen an Tragflügeln gibt es Ansätze, um insbesondere den Schallentstehungsmechanismus, der mit solchen Zuströmbedingungen verknüpft ist, den sog. Zuströmturbulenzschall, zu verringern. Dabei wird die üblicherweise gerade Vorderkantengeometrie sinusförmig ausgeführt. Die Schallabstrahlung von Tragflügeln konnte dadurchmaßgeblich verringert werden. Um die Wirksamkeit solcher Vorderkantenmodifikationen zur Schallreduzierung von Axialventilatoren zu überprüfen, wurde eine Parameterstudie mit sinusförmigen Vorderkanten an Ventilatoren mit unterschiedlicher Sichelung - vorwärts-, rückwärts- und ungesichelt - durchgeführt. Neben dem Referenz-Ventilator mit gerader Vorderkante wurden vier weitere Konfigurationen mit sinusförmigen Vorderkanten (mit unterschiedlichen Parametern für Wellenlänge und Amplitude der Sinusfunktion) an den vorwärts-, rückwärts- und ungesichelten Ventilatoren hinsichtlich ihrer aerodynamischen und akustischen Eigenschaften untersucht. Die Ergebnisse zeigen, dass sowohl der Druckaufbau als auch der Wirkungsgrad durch die modifizierten Vorderkanten bei allen Sichelungsarten verbessert wird. Des Weiteren wird die Schallemission durch die modifizierten Vorderkanten deutlich verringert. Dies zeigt sich in einer Reduzierung der breitbandigen und auch der tonalen Schallanteile. Die Verbesserung der aerodynamischen und auch der akustischen Eigenschaften ist dabei vor allem von derWellenlänge der Sinusfunktion abhängig.<br
Keywords: Axialventilator; Vorderkante; Akustik; Sichelung; Zacken